The Use of Serum Endothelin1and Myoglobin in the Evaluation of Renal Injury in Methamphetamine Abusers - Shahbaa Waheed Sami; Basil O. Saleh; Muataz A AL-Qazzaz (Institute of Medico-legal Publications Pvt Ltd, 2021)
Methamphetamine is a type of psychoactive drug. It is a widely abused synthetic stimulant. Long-termexposure to methamphetamine leads to kidney damage and subsequently a gradual reduction in its function.Methamphetamine toxicity is the trigger of creatinine increase. Myoglobin is released to the blood circulationfrom injured muscle tissues after its long-term use and forms deposits in the renal tubules. Endothelin-1 isknown as the most powerful recognized renal vasoconstrictor. Estimated glomerular filtration rate (eGFR) isthe most sensitive index to determine kidney function, and it is an important indicator of early diagnosis ofrenal injury. The study was conducted on 48 patients (study group) and 36 control group; their age range wasbetween 18-40 years. Those with history of chronic kidney disease, cardiovascular diseases, hypertension,and alcohol addiction were excluded from the study. Fasting venous plasma samples were used to measurecreatinine, urea, eGFR, myoglobin and ET-1. The estimated glomerular filtration rate (eGFR) was calculatedusing the creatinine-based chronic kidney disease epidemiology collaboration (CKD-EPI) formula. Themean (±SD) values of serum urea and creatinine levels of abuser subjects were significantly higher thanthose of control subjects. The mean (±SD) value of eGFR of abuser individuals was significantly lowerwhen compared with that of the control group (p < 0.0001). In addition, inabuser subjects we observed asignificant increase in mean values of serum levels of endothelin1 (p< 0.015) and myoglobin (p< 0.0001)in comparison with those of control group. Significant negative correlations between eGFR and duration ofmethamphetamine abuse (p< 0.0002) as well as a significant positive correlation between serum creatininelevels and duration of methamphetamine abuse (p< 0.0004) were noted in the patient’s group. Moreover,there was a significant positive correlation between serum myoglobin concentrations and endothelin1 levels(p<0.00001). This study concluded that abusers of methamphetamine need to be screened periodically forkidney function and measurements of their serum creatinine level as well as eGFR value. Both endothelin 1and myoglobin are important indicators of methamphetamine-induced kidney damage.